(untitled) (Al-Qamar, 2021)
Tawheed is the fundamental belief of Muslims. The common theme of preaching of all prophets, including the Last Prophet Hazrat Muhammad (Peace be upon him ) was the belief of Tawheed. The edifice of Quranic teachings is also based on Tawheed. In every period of time, saints and scholars preached for Tawheed and with their utmost efforts and abilities they have penetrated the belief of Oneness of Allah in the hearts of people. Tawheed e Ilahi means conviction in Oneness of Allah, which must be manifested both by words and actions. It implies that Allah is the only omnipotent and worthy of worship and no creature is parallel to Him. The Sufis have described the belief of monotheism in mysticism books in a simple, easy and lucid way. Later on, when logic, philosophy and complex dialectic of theology were assimilated in Islamic Sciences, Sufis’ way of thinking also became diverse under that influence. The commentators of Quran have explained the belief of Tawheed in the light of injunctions in Surah Ikhlas and other Ayats in the same way as Sufis have done. There is a similarity between the Opinions of commentators of Quran and the thoughts of Sufis. If there is any difference, then it is just in style of narration. In spite of the difference in words, the essence of message is same. And the research and inquisition for truth of Sufis and commentators of Quran are valuable and commendable in promoting and communicating the belief of monotheism.